Flow-Through Share as a fiscal mechanism to encourage exploration in the mining industry: An in-depth study of the Canadian Legislation for prospective implementation in South Africa - Sauls, Richard (Department of Finance and Tax, 2025)
An element of great concern in the South African economy is the underwhelming amount of investment in mining exploration. The South African government through the Department of Mineral Resources and Energy (DMRE) formulated a strategy to combat the deterioration discerned in mining investment. The strategy tables the introduction of a flow-through share incentive in South Africa, to stimulate investment in mining exploration (DMRE, 2022:3). Flow-through shares, equity instruments in mining and petroleum companies, are subject to unique tax rules established through agreements between investors and investees (Jog, Lenjosek & McKenzie, 1996: 1017). This research aims to comprehensively analyse flow-through share arrangements, offering insights into their issuance, technical tax aspects, and additional incentives. Furthermore, the study identifies deficiencies in the South African mining taxation landscape, presenting recommendations to incentivise further investment in mining exploration. The research begins with an in-depth examination of regulatory and legislative requirements, progressing from defining flow-through shares to exploring their intricate mechanics. The research provides a practical overview and understanding of the design, tax consequences and benefits of a flow through share arrangement, with specific focus on capital gains implications. The study also conducts a detailed analysis of the South African Income Tax Act, highlighting shortcomings of the legislative provisions regarding incentives incorporated within the legislation. The findings underscore the potential significant benefits to the South African mining industry as it improves the Mining Attractiveness Index (MAI) and leveraging associated tax advantages. Despite the multifarious benefits, the research acknowledges specific areas of concern, particularly regarding capital gains tax (CGT), which may deter investment. Additionally, the study provides indication that the government needs to introduce alternative incentives, as several benefits are reaching sunset clauses. Consequently, resulting in the deterioration of the Income Tax incentives to invest in mining.